PENGEMBANGAN MEDIA SMART ROULLETE UNTUK MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN - Rohyana Fitriani; Novitasari Utami; Suhirman Suhirman (Universitas Hamzanwadi, 2021)
The purpose of this study was to develop a smart roulette learning media to improve the social and emotional aspects of children aged 5-6 years. The development model used is Borg and Gall which consists of six stages. The products developed are validated by a team of experts. The small scale subjects were 5 children and the large scale subjects were 15 children. The instrument used to collect data is an observation sheet. The results showed that the results of the media expert's validation obtained a score of 42 with an average value of 5.25 in the